High voltage transformation ratio using matrix converter / N. Mahendran and Dr. G. Gurusamy - Mahendran, N.; Gurusamyq, G. (Dr.) (UiTM Press, 2010)
In this paper, two similar Fuzzy Logic Controllers are developed for ac/ac matrix converters. Furthermore, total harmonic distortion (THD) is reduced significantly. Output voltage approaches the input voltage with reduced loss. A Matlab / Simulink simulation analysis of the Matrix Converter system is provided. The design and implementation of fuzzy controlled Matrix Converter is described. This AC-AC system is proposed as an effective replacement for the conventional AC-DC-AC system which employs a two-step power conversion with high voltage transformation ratio.